Scientific Methods of Analysis to Improve Occupational Safety by the Sanitary and Hygienic Condition of Industrial Premises - Rakhmonberdievich, Yuldashev Orynbai; Razzokov, Khabib Kholikovich (European Journal of Life Safety and Stability (2660-9630), 2022)
Reconstruction of textile and light industries shows that the greatest effect of noise reduction can be achieved by applying a set of measures consisting of replacing old equipment with new, less noiseless, when installing (to reduce structural noise in a building) insulating gaskets, as well as lining ceilings and walls with sound-absorbing material. This scientific approach allows you to reduce the noise of the premises. Reduction of industrial noise in workshops from 103 to 90 dB allowed to reduce the amount of hearing loss in workers at river frequencies from 8 dB, and at a frequency of 4000 Hz by 12 dB.